Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) Industri Rumah Tangga Tahu di Mojogedang Kab. Karanganyar: Tantangan dan Peluang - Sulistya; Rohwiyati; Raisya Ramadhani Rachim (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service activity focuses on developing tofu Micro, Small and Medium Enterprises (MSMEs) in Mojogedang District. MSMEs know that this region has great potential to support the local economy, but faces various challenges such as limited production technology, less than optimal marketing and ineffective business management. This activity aims to increase the capacity and competitiveness of tofu MSMEs through training, technical assistance and development of marketing networks. The methods used in this activity include training on efficient and environmentally friendly tofu production technology, assistance in implementing product innovation and business management, as well as developing effective marketing strategies. The results of this activity show an increase in the knowledge and skills of MSME actors in the production and management of tofu businesses, as well as an increase in their access to more efficient production technology. Apart from that, this activity also succeeded in expanding the marketing network for tofu products from Mojogedang, thereby increasing the income and economic welfare of the local community. Thus, this activity provides significant benefits for tofu MSMEs, the community and other related parties, as well as supporting sustainable local economic improvement programs. Keywords: MSMEs, Production Technology, Marketing, Product Innovation